Hubungan Kebiasaan Sarapan, Durasi Tidur dan Tingkat Stres dengan Kejadian Obesitas Pada Mahasiswa Jurusan Kesehatan di Politeknik Negeri Jember - Putri, Miftachul Nur Abrilia Febriyanti (JURNAL NUTRISIA, 2025)
One group that is prone to nutritional problems is university students. One lifestyle that can affect nutritional status is breakfast habits. In addition, short sleep time can also affect nutritional status. For some people, eating is a way to cope with stress, so a person's psychological state, i.e., stress, can affect nutritional status. The aim of this study was to clarify the relationship between breakfast habits, sleep time, stress levels and obesity rates among university students. This type of study uses analytical observational technique with cross-sectional design. Purposive sampling was used in the sampling technique in this study. The population of this study consisted of active students of the Faculty of Health Sciences at Jember State University of Technology, with a total sample size of 98. Statistical analysis using SPSS application and Spearman rho test. Conclusion: Based on the analysis performed, the results show that there is a relationship between breakfast habits (p=0.000, r = - 0.491) and sleep duration (p = 0.011, r = - 0.255) and obesity rates among students. There is no relationship between stress levels (p=0.370, r=0.092) and obesity rates among students.